Financial Literacy, Management Practices of Public Elementary School Teachers: An Input to Teacher Financial Management Plan (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study focused on analyzing and scrutinizing the financial literacy, management practices of public elementary teachers. This study also determined it is deemed necessary to study the financial literacy of the teachers because public teachers positioned themselves as one of the largest members of both local and national government and serve as molder and role model of the next generation. The study concise method of analysis. Descriptive research method is a purposeful process of collecting, evaluating, classifying and tabulating data under prevailing conditions, procedures, attitudes, methods, patterns and cause-effect relationships, and making appropriate and reliable analysis of such data with or without the assistance of statistical method. There were200teacher respondents from big school and 74 teacher respondents from medium school in the City Schools Division of Cabuyao with the total of 274. The results show that there is no significant difference in the financial literacy of the respondents when they are classified according to the demographic profile. The results show that there is no significant difference in the financial literacy of the respondents when they are classified according to the demographic profile. Hence, the hypothesis was accepted